Academic staff recruitment and development in private universities in Vietnam: in comparison with public universities - Lam, Chau Diem (2009)
Quality of education remains a problem in higher education in Vietnam and can be considered one of the most crucial and greatest challenges that institutions are now facing and which they need to make great efforts to resolve. Among the various factors that influence this is the quality of the teaching staff in higher education institutions. Due to the shortage of highly qualified academic staff, higher education institutions of both public and private are competing both with each other, and with organisations outside the educational sector, in recruiting academic staff. The thesis explores current issues of staffing and academic staff development in private universities in Vietnam, the policies implemented by them to promote academic staff development, and the extent to which these policies have proved to be effective in raising teaching quality.